2020
DOI: 10.1080/1828051x.2020.1773949
|View full text |Cite
|
Sign up to set email alerts
|

Effect of betaine, a methyl group donor, on broiler chicken growth performance, breast muscle quality characteristics, oxidative status and amino acid content

Abstract: This study was aimed to investigate the effect of feed supplemented with betaine on broiler chickens' growth and slaughter performance, breast muscle histomorphometric and physicochemical properties, oxidative status and amino acid content. A total of 1000 1-day-old Ross 308 broiler chickens were divided into four treatments. Control group chickens were fed with standard compound diet (SCD), the chickens from experimental groups B1, B2 and B3 receiving SCD supplemented with 1 g/kg (B1), 2 g/kg (B2) and 3 g/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Similar to the current findings, the above authors [3637] reported reduced oxidative stress with Bet supplementation in broilers fed the low-Met diet. Reduction in breast muscle oxidative process with Bet supplementation is one of the mechanisms of reduced LP in the serum of broilers fed MD supplemented diets [2728]. Similar to the current findings, significant reduction in LP was reported with Bet supplementation in broiler diet [9,2728].…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 86%
See 2 more Smart Citations
“…Similar to the current findings, the above authors [3637] reported reduced oxidative stress with Bet supplementation in broilers fed the low-Met diet. Reduction in breast muscle oxidative process with Bet supplementation is one of the mechanisms of reduced LP in the serum of broilers fed MD supplemented diets [2728]. Similar to the current findings, significant reduction in LP was reported with Bet supplementation in broiler diet [9,2728].…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 86%
“…Similarly, the albumin concentration in all the MD supplemented groups improved similar to those fed the CD. Similar to these observations, improvement in FEwas observed with supplementation of Bet [8,2728] or FA [2829] to diet containing sub-optimal concentrations of Met.…”
Section: Serum Protein Fractionssupporting
confidence: 78%
See 1 more Smart Citation
“…Choline was also a precursor of the neurotransmitter acetylcholine, PC, and betaine, involved in several critical physiological functions ( 52 ), such as modulation of gene expression, synaptic plasticity, and cholinergic signaling ( 50 , 51 ). Betaine is a direct methyl donor, which can be obtained from diet or transformed from choline ( 53 ). A recent study revealed that the concentrations of choline and betaine were significantly positive and a trending positive correlation with depression scores (EPDS), respectively ( 54 ), and betaine was associated with the severity of depression of psychiatric patients, who were diagnosed with major depressive disorder (MDD) or bipolar disorder ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…When using the preparation of succinic acid on broiler chickens, an increase in the essential amino acids content in the muscular tissue proteins of experimental groups' chicks in relation to control indicators was observed [17]. Supplements of betaine in the broiler chickens' diet affected the increase in the essential amino acids content in meat [18]. Carnitine introduction to the diet protects branched chain amino acid against oxidation in tissues [19].…”
Section: Fig 2 Content Of Dispensable Amino Acids In Broiler Chickens' White Meat Protein Mg/100 G (N=9)mentioning
confidence: 99%